Active materials for electric double layer capacitors

By mixing activated carbon with a high proportion of mesopores into micropore-based activated carbon, the EDLCs achieve improved cycle and rate characteristics, addressing the limitations of existing EDLCs in maintaining performance over repeated cycles.

JP7670312B2Active Publication Date: 2025-04-30AKITA UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021036667
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2025-04-30
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Existing electric double layer capacitors (EDLCs) face challenges in maintaining high specific capacitance and cycle life due to electrolyte decomposition and pore blockage, which reduces their performance over repeated charge/discharge cycles.

Method used

The use of a mixed active material composed of activated carbon mainly composed of micropores and mesopores, with a weight ratio of mesopores to the sum of micropores and mesopores ranging from 10 to 50 wt%, effectively improves the cycle and rate characteristics of EDLCs without increasing internal resistance.

Benefits of technology

This approach allows EDLCs to maintain high specific capacitance even after numerous charge/discharge cycles, enhances rate characteristics with minimal dependence on current density, and simplifies manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670312000006
    Figure 0007670312000006
  • Figure 0007670312000007
    Figure 0007670312000007
  • Figure 0007670312000008
    Figure 0007670312000008
Patent Text Reader

Abstract

To provide active material for electric double layer capacitor (EDLC) for manufacturing an EDLC having an excellent characteristic, especially provide active material for EDLC enabling elongation of cycle lives of the EDLC.SOLUTION: Active material for an electric double layer capacitor is provided which is comprised of active carbon composed mainly of micro holes and active carbon composed mainly of meso holes. The weight ratio between active carbon composed mainly of micro holes and active carbon composed mainly of meso holes, satisfies an equality " (active carbon composed mainly of meso holes) / (active carbon composed mainly of micro holes + active carbon composed mainly of meso holes)=10-50 wt% " and the weight ratio of the two types of active carbon to the whole active material is equal to or more than 90 wt%. According to the invention, the active material for the electric double layer capacitor can be provided which can maintain high specific electrostatic capacity even when exposed to many charging / discharging cycles, that is, which has excellent rate characteristic.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active material for an electric double layer capacitor, and more particularly to an active material for an electric double layer capacitor that can realize an electric double layer capacitor having excellent charge / discharge cycle characteristics. [Background technology]

[0002] An electric double layer capacitor (EDLC) is an electricity storage device that utilizes the electric double layer that occurs at the boundary between the electrodes and the electrolyte. The electricity storage principle is based on the physical adsorption and desorption of ions on the electrode surface, so it has the advantages of little deterioration, a long life, rapid charging and discharging, high output density, and high safety due to no structural or chemical changes.

[0003] An EDLC is composed of electrodes, a separator, an electrolyte, and an exterior case. Of these, the electrodes are made up of an active material (mainly activated carbon), a conductive additive, a binder, and a current collector. In principle, the electrical capacity of an EDLC depends on how many ions in the electrolyte can be adsorbed onto the electrode surface, so it can be said simply that the larger the surface area of ​​the electrode, the greater the capacity. Activated carbon is used to meet this requirement. However, using activated carbon with a large specific surface area as an electrode material does not necessarily increase the capacity of the EDLC. This is because if the specific surface area of ​​the activated carbon becomes extremely large, the size of the pores becomes too small and the ions in the electrolyte cannot move freely within the pores. In this situation, studies are being conducted on activated carbon with a composite of micropores and mesopores to find the optimum specific surface area and pore size for electric double layer capacitor electrodes (for example, Patent Document 1 and Patent Document 2).

[0004] On the other hand, there are known examples of using different types of activated carbon mixed together as an active material for electric double layer capacitors. Examples of such mixed activated carbons include mixing coconut shell activated carbon, which is mainly microporous, with alkali-activated activated carbon to adjust the oxygen-containing functional groups remaining on the surface of the activated carbon, which causes electrode deterioration, and aiming to improve durability, although the effect is small (Patent Document 3), and adjusting the variation in capacitance caused by coconut shell activated carbon, which is a natural product (Patent Document 4). Furthermore, there is known a product in which one of wood, bamboo forest, and rice husk activated carbon is used as the first activated carbon and fibrous cotton activated carbon is used as the second activated carbon, with the aim of reducing manufacturing costs and facilitating molding (Patent Document 5). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. WO2018 / 092721 [Patent Document 2] Patent Publication No. 2014-165435 [Patent Document 3] Patent Publication No. 2005-243933 [Patent Document 4] JP2007-67034A [Patent Document 5] Patent Publication No. 2016-18808 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an active material for an electric double layer capacitor (EDLC) for producing an EDLC having excellent characteristics, and in particular to provide an active material for an EDLC that can extend the cycle life of the EDLC. By the way, the principle of EDLC is physical adsorption and desorption of ions on the electrode surface, so no chemical change is involved and theoretically the cycle life is infinite. Therefore, there has been little research on extending the cycle life, and at best, research has been done on controlling the number of oxygen-containing functional groups that are the starting point of the decomposition reaction of the electrolyte. However, in reality, EDLC also deteriorates as it is repeatedly charged and discharged. When the decomposition reaction of the electrolyte is triggered and the decomposition products generated at that time accumulate on the surface layer of the activated carbon electrode, the pores are blocked and the internal resistance increases, and the capacitance of the electrode gradually decreases. This invention is also new in that it tackles a problem that has not been considered a problem much and devise a solution in a way other than controlling the number of oxygen-containing functional groups. A further object of the present invention is to improve cycle characteristics and at the same time realize excellent rate characteristics with small current density dependence of specific capacitance, and further provide an active material for EDLC that can be easily produced. [Means for solving the problem]

[0007] In order to achieve the above-mentioned object, the inventors conducted various studies and discovered that, as an active material for EDLC, by mixing activated carbon mainly composed of micropores with activated carbon mainly composed of mesopores, which have larger pore sizes, it is possible to maintain a high specific capacitance of the electrode even when exposed to numerous charge / discharge cycles, in other words, it is possible to improve the cycle characteristics of EDLC, and thus arrived at the present invention. That is, the present invention is as follows. 1. Active materials for electric double layer capacitors consisting of activated carbon mainly composed of micropores and activated carbon mainly composed of mesopores. 2. The active material for electric double layer capacitors according to 1 above, wherein the weight ratio of the activated carbon mainly composed of micropores and the activated carbon mainly composed of mesopores is "(activated carbon mainly composed of mesopores) / (activated carbon mainly composed of micropores+activated carbon mainly composed of mesopores)=10-50 wt%", and the combined weight ratio of the two types of activated carbon to the entire active material is 90 wt% or more. 3. The active material for electric double layer capacitors according to 1 or 2 above, wherein the activated carbon mainly having mesopores is rice husk activated carbon. 4. An electric double layer capacitor using, as one or both electrodes, an electrode in which the active material for an electric double layer capacitor according to any one of 1 to 3 above is used as an active material. 5. The electric double layer capacitor according to claim 4, wherein the electrolytic solution used in the electric double layer capacitor is an organic electrolytic solution. 6. The electric double layer capacitor according to claim 4, wherein the electrolyte used in the electric double layer capacitor is an ionic liquid. Effect of the Invention

[0008] According to the present invention, it is possible to provide an active material for an electric double layer capacitor, which can maintain the specific capacitance of the electrode high even when exposed to numerous charge / discharge cycles, i.e., can improve the cycle characteristics, has excellent rate characteristics, and can be used to manufacture an electric double layer capacitor by a relatively simple manufacturing method. [Brief description of the drawings]

[0009] [Figure 1] The structural diagram of activated carbon is shown below. [Diagram 2] The particle size distribution of each activated carbon is shown. [Diagram 3] An outline of the Nyquist diagram is shown. [Figure 4] The rate characteristics of the RHAC-doped EDLC are shown. [Diagram 5] The specific capacitance-cell voltage characteristics (TEA·BF4 / PC) during rate testing of RHAC-doped EDLC are shown. [Figure 6] The specific capacitance-cell voltage characteristics (EMIm·BF4) during rate testing of RHAC-added EDLC are shown. [Figure 7] The rate characteristics of the AP15-added EDLC are shown. [Figure 8] The specific capacitance-cell voltage characteristics (TEA·BF4 / PC) of AP15-doped EDLC during rate testing are shown. [Figure 9] The specific capacitance-cell voltage characteristics (EMIm·BF4) during rate testing of AP15-added EDLC are shown. [Figure 10] The cycle characteristics of the RHAC-added EDLC are shown. [Figure 11] The specific capacitance-cell voltage characteristics (TEA·BF4 / PC) of the RHAC-added EDLC in cycle tests are shown. [Figure 12] The specific capacitance-cell voltage characteristics (EMIm·BF4) of the RHAC-added EDLC in cycle tests are shown. [Figure 13] The cycle characteristics of the AP15-added EDLC are shown. [Figure 14] The specific capacitance-cell voltage characteristics (TEA·BF4 / PC) of the AP15-added EDLC in cycle tests are shown. [Figure 15] The specific capacitance-cell voltage characteristics (EMIm·BF4) of the AP15-added EDLC in a cycle test are shown. [Figure 16] The impedance characteristics (DC bias voltage: 0 V) ​​of the RHAC-added EDLC before and after the cycle test are shown. [Figure 17] The impedance characteristics (DC bias voltage: 2.5 V) of the RHAC-added EDLC before and after the cycle test are shown. [Figure 18] The impedance characteristics (DC bias voltage: 0 V) ​​of the AP15-added EDLC before and after the cycle test are shown. [Figure 19] The impedance characteristics (DC bias voltage: 2.5 V) of the AP15-added EDLC before and after the cycle test are shown. [Figure 20] The SEM images of the surface of an electrode containing RHAC before and after a charge-discharge test when TEA·BF4 / PC was used as the electrolyte are shown. [Figure 21] The SEM images of the RHAC-added electrode before and after a charge-discharge test when EMIm·BF4 was used as the electrolyte are shown. [Figure 22] The SEM images of the surface of the AP15-added electrode before and after a charge-discharge test when TEA·BF4 / PC was used as the electrolyte are shown. [Diagram 23] The SEM images of the surface of the AP15-added electrode before and after a charge-discharge test when EMIm·BF4 was used as the electrolyte are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. 1. Activated carbon used as the active material The electrodes of an electric double layer capacitor are composed of an active material that takes in and releases ions, a conductive assistant that increases the conductivity of electrons, a binder that binds the two together, and a current collector that is coated with a mixture of these. Activated carbon with a large specific surface area is mainly used as the active material for electric double layer capacitors so that as many ions in the electrolyte as possible can be adsorbed onto the electrode surface.

[0011] The present invention relates to an active material for electric double layer capacitors, which is composed of activated carbon mainly composed of micropores and activated carbon mainly composed of mesopores, in which activated carbon mainly composed of micropores is mixed with activated carbon mainly composed of mesopores as an additive. By adding activated carbon mainly composed of mesopores to activated carbon mainly composed of micropores, it is possible to improve the cycle characteristics of EDLC without deteriorating the rate characteristics, which indicate the current density dependence of specific capacitance. However, no such report has been published to date, and the present invention marks the beginning of a method for improving cycle characteristics. Until now, it was thought that the rate characteristics could be improved by gradually drawing ions from larger pores into smaller pores, allowing the ions to be guided to the depths of the pores. To achieve this, micropores and mesopores must exist in a composite manner, rather than being present alone. Despite this, the present invention has been developed, in which an active material in which activated carbon particles mainly made up of micropores and activated carbon particles mainly made up of mesopores coexist, rather than a single type of activated carbon in which micropores and mesopores are compositely formed, is a mixture of different types of activated carbon, and shows excellent performance as an electrode for EDLC. Micropores are pores with a width of 2 nm or less, and mesopores are pores with a width of 2 to 50 nm (the widths are illustrated in [Figure 1]). Activated carbon mainly made up of micropores is activated carbon with many developed micropores, but may contain pores with other widths. Activated carbon mainly made up of mesopores is also activated carbon with many developed mesopores, but may contain pores with other widths (Reference: [Examples] [Table 1] Activated carbon mainly made up of micropores also has a certain degree of mesopores, and activated carbon mainly made up of mesopores also has a certain degree of micropores). Mainly made up of micropores is a state in which the micropore volume has a volume of more than half of the total pore volume, and the same is true for mesopores. Since activated carbon "mainly made up of" micropores and activated carbon "mainly made up of" mesopores are mixed, the value of "micropore volume:mesopore volume" does not completely match the mass ratio of each of the mixed activated carbons, but it can be considered that it is roughly the same.

[0012] The weight ratio of the activated carbon mainly composed of micropores and the activated carbon mainly composed of mesopores is more preferably "(activated carbon mainly composed of mesopores) / (activated carbon mainly composed of micropores+activated carbon mainly composed of mesopores)=10 to 50 wt%, and particularly preferably "10 to 30 wt%." When the proportion of activated carbon mainly composed of mesopores is high, the specific surface area of ​​the mixed active material is reduced, leading to a decrease in ion adsorption sites, so it is more preferable that the proportion of activated carbon mainly composed of mesopores is below a certain level. If the content is at least "10 to 50 wt %, the specific capacitance will not decrease even if the charge / discharge current density increases, and the specific capacitance can be maintained high even when exposed to 10,000 to 100,000 or more charge / discharge cycles.

[0013] Examples of activated carbon mainly composed of micropores include coconut shell activated carbon, charcoal activated carbon, resin activated carbon, coal activated carbon, and alkali-activated activated carbon, while examples of activated carbon mainly composed of mesopores include rice husk activated carbon, sawdust activated carbon, and zinc chloride activated carbon.

[0014] Rice husk activated carbon is activated carbon that uses rice husks as a carbon source, and is obtained by carbonizing rice husks, removing some or most of the silica from the carbonized product, or by carbonizing the product from which the silica has already been removed, and then subjecting it to gas activation using water vapor or carbon dioxide.

[0015] The active material for electric double layer capacitors of the present invention is composed of activated carbon mainly composed of micropores and activated carbon mainly composed of mesopores, but does not exclude the case where other materials, such as activated carbon mainly composed of macropores or carbon nanotubes, are mixed in small amounts. In this case, it is more preferable that the weight ratio of the activated carbon mainly composed of micropores and activated carbon mainly composed of mesopores to the entire active material is 90 wt% or more.

[0016] 2. Application to the positive electrode of hybrid capacitors The electrode for EDLC is naturally also for the positive electrode of a hybrid capacitor. In a hybrid capacitor, the principle of adsorbing and desorbing ions in an electrolyte solution inside the pores of activated carbon is also used, and the active material discovered in the present invention can be used as a positive electrode material for a hybrid capacitor in the sense that an organic electrolyte solution or an ionic liquid is used as the electrolyte solution. In other words, the active material of the present invention includes the active material even when used for the positive electrode of a hybrid capacitor.

[0017] 3. Components other than the active material of the electrode Other components of the electrode, such as a conductive assistant, a binder, and a current collector, can be those that are commonly used and are not particularly limited. The weight ratio of the components is preferably 5 to 15 parts by weight of the binder, and more preferably 5 to 15 parts by weight of the binder, relative to 70 to 90 parts by weight of the active material.

[0018] 4. Components other than electrodes of EDLC When an EDLC cell is assembled using electrodes using the active material of the present invention, there is no particular limitation on the electrolyte and separator used. The electrolyte may be an organic electrolyte or an ionic liquid. The addition of mesopore-based activated carbon can improve the cycle characteristics of EDLC without deteriorating the rate characteristics, but when an ionic liquid is used as the electrolyte, the rate characteristics are actually improved compared to when no mesopore-based activated carbon is added. That is, when an ionic liquid is used as the electrolyte and the weight ratio of the micropore-based activated carbon and the mesopore-based activated carbon is more preferably "(mesopore-based activated carbon) / (micropore-based activated carbon + mesopore-based activated carbon) = 10 to 50 wt%, more preferably "10 to 30 wt%, both the rate characteristics and the cycle characteristics can be improved compared to when no mesopore-based activated carbon is added. An example of an organic electrolyte is TEA·BF 4 / PC, TEMA·BF 4 / PC, SBP·BF 4 / PC, etc., and furthermore, TEA·BF, in which the solvent propylene carbonate (PC) was replaced with acetonitrile (AN), 4 / AN, TEMA·BF 4 / AN, SBP·BF 4 Examples of ionic liquids include EMIm BF 4 , EMIm·FSI, EMIm·TFSI, etc. The separator may be made of paper or resin, which is commonly used for electric double layer capacitors.

[0019] 5(1) Consideration of the theory behind the improvement of the cycle characteristics of EDLC The addition of activated carbon mainly composed of mesopores to activated carbon mainly composed of micropores can improve the cycle characteristics of EDLCs without deteriorating the rate characteristics, which indicate the current density dependence of specific capacitance, for the following reasons. Coconut shell activated carbon is an activated carbon mainly composed of micropores. In addition, when the oxygen content of the surface of the activated carbon electrode was evaluated using an energy dispersive X-ray spectroscopy (EDX), oxygen was found to be present, and decomposition of the electrolyte also occurs in coconut shell activated carbon. In this case, the decomposition residue of the electrolyte, especially the polymerized decomposition residue, cannot be absorbed by the micropores with a width of 2 nm or less, and accumulates on the outermost layer of the electrode. This thick film reduces the accessibility of the electrolyte to the pores in the activated carbon and also has high electrical resistance. Therefore, a high voltage is shared by the film during the charge and discharge process. Therefore, the voltage shared by the electric double layer that contributes to the accumulation of charge is reduced, and the specific capacitance is reduced. The surface layer of the film contains a large amount of oxygen-containing functional groups and decomposed electrolytes, which further promotes the decomposition of the electrolyte and grows the film further. The decomposition residue deposition layer then fills the gaps between the activated carbon particles. This can also be confirmed from the SEM image of the deteriorated negative electrode made of 100% coconut shell activated carbon (details are described in [Example 2] 4. Analysis of the electrode by scanning electron microscope). As a result, the specific capacitance gradually decreases as the number of charge / discharge cycles increases. It is believed that the EDLC active material of the present invention, by incorporating activated carbon mainly composed of mesopores as an additive, captures the decomposition residue of the electrolyte in the mesopores so that it does not become the starting point for film formation, and prevents the growth of a film that causes a decrease in specific capacitance, thereby improving the cycle characteristics of the EDLC.

[0020] (2) Consideration of the reason why the addition of rice husk activated carbon could improve cycle characteristics In addition, rice husk activated carbon (hereinafter referred to as RHAC) contains many oxygen atoms, and the many oxygen-containing functional groups accelerate the decomposition of the electrolyte, which tends to cause the decomposition residue to accumulate. From this perspective, it is presumed that high cycle stability cannot be expected even if RHAC is added. However, as in the present invention, the addition of RHAC can improve the cycle characteristics, which is surprising. Since RHAC has a mesoporous structure, the polymerized decomposition residue is adsorbed in the mesopores of RHAC, and the carbon substrate of the activated carbon can be maintained in a state exposed to the electrolyte. Although RHAC has a high oxygen content, the amount is not enough to significantly promote the decomposition of the electrolyte, and the decomposition residue is stored in the mesopores. Therefore, it is considered that the coating on the outermost layer of the electrode is less likely to grow, and the cycle characteristics can be improved. The situation in which the coating did not grow can also be confirmed from SEM images of YP-50F 80% RHAC 20%, YP-50F 60% RHAC 40%, and RHAC 100% (details are described in [Example 2] 4. Analysis of the electrode by scanning electron microscope).

[0021] (3) When using an ionic liquid as the electrolyte, the EDLC with mesoporous activated carbon added showed a smaller current density dependence of the specific capacitance and better rate characteristics than the EDLC without the activated carbon. It is believed that the mesopores contained in the mesopore-based activated carbon mitigate the effects of the high ionic conductivity and high viscosity (ionic interactions) of the ionic liquid, allowing sufficient ion adsorption and desorption on the electrode surface even at high current densities compared to additive-free EDLC.

[0022] 6(1) Electrode manufacturing The electrodes were made by mixing activated carbon powder for EDLC electrodes, which is a mixture of activated carbon with mainly micropores and activated carbon with mainly mesopores, a conductive additive, a binder, and water, and then coating the mixture on aluminum foil and drying it in an oven. The electrodes were made by punching this into the appropriate shape. Compared to the conventional method of producing activated carbon that combines micropores and mesopores, this method is relatively easy to produce since it only requires adding different activated carbon to the raw materials, and since it is only necessary to adjust the ratio of activated carbon added, it is also relatively easy to adjust the ratio of micropores and mesopores. These points can also be considered major advantages.

[0023] (2) Assembly of EDLC cell The completed electrodes are then used to assemble an EDLC cell using a separator, electrolyte, and outer casing. EXAMPLES

[0024] Example 1 Assembly of an Electric Double Layer Capacitor 1. Preparation of Activated Carbon Electrode In preparing the activated carbon electrode, coconut shell activated carbon YP-50F (Kuraray Chemical Co., Ltd., hereafter YP-50F), rice husk activated carbon RHAC (hereafter RHAC), and phenolic resin activated carbon AP15 (AT Electrode Co., Ltd., hereafter AP15) were used. The RHAC used was produced by referring to the method of producing rice husk activated carbon only without adding sugars, which is described in a document (Seiji Kumagai, Masashi Sato, Daisuke Tashima, Electrical Double-layer Capacitance of Micro-and Mesoporous Activated Carbon Prepared from Rice Husk and Beet Sugar, Electrochimica Acta, 2013, 114, pp. 617-626.). Specifically, the rice husk was carbonized, and the carbonized material was immersed in an alkaline aqueous solution to remove silica, washed, and activated with water vapor. Thereafter, the product was immersed in an alkaline aqueous solution again, washed, dried, and crushed to produce the product. The pore properties of each activated carbon were evaluated using a gas adsorption analyzer (Autosorb 3B, Quantachrome). The results are shown in Table 1. YP-50F and AP15 had many micropores of 2 nm or less, while RHAC had many mesopores of 2 nm or more. YP-50F had a high specific surface area because it had many micropores, followed by AP15 and RHAC. RHAC had many mesopores, so it had a large total pore volume but a small specific surface area. In addition, the average pore width was 3.8 nm, and RHAC had pores that were on average about twice as wide as YP-50F and AP15. [Table 1] Furthermore, the particle size of each activated carbon was measured using a laser diffraction particle size distribution analyzer (SALD-200V, Shimadzu Corporation). The results are shown in Figure 2 and Table 2. Regarding particle size distribution, the horizontal axis is particle size and the vertical axis is relative particle amount. From Figure 2, the particle size distribution of RHAC and AP15 used as additives is roughly the same, and from Table 2, the average particle size is approximately 10 μm, and 50% D is approximately 11 μm. Here, 50% D corresponds to the particle size when the number of particles reaches 50% when accumulating the number of particles starting from the smallest particle size. [Table 2] Activated carbon powder for EDLC electrodes was prepared by adding RHAC or AP15 to YP-50F in four mass ratios of 100:0, 80:20, 60:40, and 0:100 (see sample names in Table 3 for a list of the samples actually prepared). Furthermore, the activated carbon powder for EDLC electrodes, conductive assistant (acetylene black, Denka Black, Denka), binder (styrene butadiene rubber (SBR), JSR), and binder with thickener function (carboxymethylcellulose (CMC), Daiichi Kogyo Seiyaku) were weighed out to a mass ratio of 80:10:5:5, distilled water was added, and the mixture was mixed using a stirrer (AR-100, Thinky Corporation) to prepare a slurry. The prepared slurry was applied to an aluminum foil with a thickness of 20 μm using a Baker-type applicator. The coated aluminum foil was dried in an oven at 100°C for 6 hours, and the dried aluminum foil was cut into a size of 12 cm long x 18 cm wide, and pressed with a 4t press machine so that the coating pressure was uniform. Then, several circular pieces with a diameter of 15 mm were punched out using a punching machine. By thoroughly removing the moisture in the electrodes, it is possible to prevent the electrolyte from reacting with the moisture and to prevent the moisture from affecting the charge / discharge characteristics of the cell. Therefore, the prepared activated carbon electrodes were inserted into a glass tube oven (GTO200, manufactured by Shibata Chemical Co., Ltd.) and dried in a vacuum at 140°C for about 3 hours to remove the moisture. The mass and thickness of the dried activated carbon electrodes were measured, and two electrodes with similar mass and thickness were selected and used in each EDLC cell.

[0025] 2. Electrolyte used The electrolyte is (C 2 H 5 ) 4 N.B.F. 4 (Tetra ethyl ammonium tetra fluoroborate,TEA・BF 4 ) diluted with propylene carbonate (PC) to 1 mol / L. 4 / PC (Kishida Chemical Co., Ltd.) and ionic liquid 1-ethyl-3-methylimidazolium tetra fluoroborate (EMIm BF 4 , manufactured by Kanto Chemical Co., Ltd.) was used.

[0026] 3. EDLC Cell Assembly In order to prevent a reaction between the electrolyte and moisture, the cells were assembled in a glove box (GBJF080R, Glove Box Japan Co., Ltd.) filled with pure argon gas. In the glove box, the negative electrode, a paper separator with a diameter of 23 mm (TF40-50, Nippon Kodoshi Kogyo Co., Ltd.), a Teflon (registered trademark) guide, a positive electrode, an electrode presser, and a spring were placed in this order in a two-electrode aluminum flat cell (Hosen Co., Ltd.), and 1 mL of organic electrolyte or ionic liquid was poured using a micropipette (P5000, F123603, Gilson, Inc.), and the cell was sealed. The punched positive and negative electrodes and the paper separator were degassed in vacuum at 140 °C for 6 hours, and then introduced into the glove box without being exposed to air. Details of the positive and negative electrodes used in each EDLC are shown in [Table 3]. [Table 3]

[0027] 4. Elemental analysis of electrode surface using energy dispersive X-ray spectrometry When oxygen-containing functional groups (such as carboxyl, phenol, and lactone groups) are present on the surface of an activated carbon electrode, decomposition reactions of the electrolyte and solvent occur, initiated by the oxygen-containing functional groups themselves and by trace water molecules in the electrolyte that are adsorbed by the oxygen-containing functional groups, resulting in the production of CO and CO 2 The internal resistance increases due to deposits caused by gas generation and polymerization of solvent molecules. Therefore, the oxygen content on the surface of the activated carbon electrode is an important indicator that determines the cycle characteristics of EDLC cells. Therefore, we analyzed the elemental composition of the undegraded electrode surfaces of 100% YP-50F, 100% RHAC, and 100% AP15 using a scanning electron microscope (SEM: VE-8800, Keyence) and an energy dispersive X-ray spectroscopy (EDX: AZtecOne & x-act EDS System, Oxford Instruments). EDX is an elemental analysis method that examines the elements and concentrations that make up an object by irradiating an object with primary rays such as electron beams or X-rays, introducing characteristic X-rays generated by the irradiation of the object with primary rays into a semiconductor detector, and determining the energy and number of electron-hole pairs generated. In this elemental analysis SEM, surface images were taken at 500x magnification at different locations, and the atomic concentration of carbon (C) and oxygen (O) was measured. The results are shown in Table 4. The oxygen content of the electrode surface made of 100% YP-50F was approximately 6 at.%, the oxygen content of the electrode surface made of 100% RHAC was approximately 12 at.%, and the oxygen content of the electrode surface made of 100% AP15 was approximately 8 at.%. The oxygen content of RHAC was 12 at.%, which was higher than that of YP-50F and AP15. From the perspective of oxygen content, it was found that activated carbon electrodes that use a lot of RHAC promote the generation of electrolyte decomposition residue, and therefore high cycle stability cannot be expected. [Table 4]

[0028] Example 2: Evaluation of charge / discharge characteristics of EDLC cells

[0029] 1. Constant current charge / discharge test To evaluate the charge / discharge characteristics of the EDLC cell, a constant current charge / discharge test was conducted. The constant current charge / discharge test consists of two tests: a rate test to evaluate stability against changes in charge / discharge current density, and a cycle test to evaluate stability against repeated charge / discharge. First, a charge / discharge test system (HJ1005SD8, Hokuto Denko Corporation) was used to perform a charge / discharge test at 0.01 to 50 mA / cm2 in the cell voltage range of 0 to 2.5 V. 2 A rate test was conducted in which a charge / discharge test was performed by increasing the current density. Detailed conditions for the rate test are shown in [Table 5]. From the amount of discharged electricity, the specific capacitance C (F / g), which is the cell's capacitance per unit mass of activated carbon, was calculated and used as a performance index for the EDLC cell. The calculation formula is shown below. Here, q (C) is the amount of charge / discharge electricity, m (g) is the mass of activated carbon for both the positive and negative electrodes, and 2.5V is the maximum cell voltage. C = q / (m × 2.5) Next, the impedance test described below was carried out. After that, using the same charge / discharge test system, the current density was set to 10 mA / cm in the same cell voltage range. 2 A cycle test was performed in which the charge / discharge test was performed for 100,000 cycles at 10,000 cycle intervals with the temperature kept constant. After the cycle test, an impedance test was performed again and the EDLC cell was disassembled. [Table 5]

[0030] 2. Electrochemical Impedance Testing To investigate the internal resistance and impedance characteristics of the EDLC cell, an electrochemical impedance test was performed using an electrochemical measurement device (HZ-5000, Hokuto Denko Corporation). A weak sinusoidal AC signal with an amplitude of 5 mV was applied to the EDLC cell simultaneously with a DC bias voltage. The DC bias voltage was set to 0 and 2.5 V. Next, the frequency of the AC signal was changed from 100 kHz to 10 mHz, and the real and imaginary components of the impedance at each frequency were measured. The impedance of the EDLC cell was obtained by measuring the impedance spectrum at each bias voltage as a Nyquist diagram drawn on a complex plane as shown in [Figure 3]. If the diameter of the capacitive semicircle on the Nyquist diagram is larger, it can be visually predicted that the charge transfer resistance has increased, that is, the electrode performance has deteriorated, and if the semicircle shifts to the right, it can be visually predicted that the solution resistance has increased, that is, the electrolyte performance has deteriorated. All charge / discharge tests and impedance tests were performed at 25°C.

[0031] 3. Constant current charge / discharge test results (1) Measurement of the rate characteristics of EDLC cells and their specific capacity-cell voltage characteristics [Figure 4] to [Figure 9] show the rate characteristics of each EDLC cell and its specific capacity-cell voltage characteristics. Regarding the graph of rate characteristics, the horizontal axis is the current density, and the vertical axis is the specific capacitance (capacitance per unit mass of activated carbon in the electrode). The graph shown is for discharging, not for charging. The graph shows current densities of 0.01, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2, 5, 10, 20, and 50 mA / cm. 2 The specific capacitance retention rate during rate testing is shown to the right of the rate characteristics. The specific capacitance retention rate is the ratio of the discharge capacitance at a certain cycle point to the initial discharge capacitance, expressed as a percentage. Since EDLCs are required to be able to handle high-speed charging and discharging, the specific capacitance at high current density is important. In the graph of specific capacity-cell voltage characteristics, the horizontal axis is specific capacity and the vertical axis is cell voltage. Here, specific capacity is the value obtained by dividing the time integrated value (amount of electricity) of current during the charging or discharging process by the total mass of activated carbon in the positive and negative electrodes. Meanwhile, specific capacitance is the value obtained by dividing the specific capacity at the completion of charging or discharging by the maximum cell voltage. Specific capacity indicates the amount of charge absorbed and released in the electrodes during the charging and discharging processes. The rate test results for each EDLC shown in [Figure 4] show that the electrolyte is TEA·BF 4 The EDLC with RHAC added to the electrolyte (EMIm BF) did not show any significant change in rate characteristics compared to the EDLC without RHAC added. 4 The EDLC using (ionic liquid) exhibited a higher specific capacitance at high current densities than the EDLC without the additive, and also showed an improved specific capacitance retention rate. [Figure 5] and [Figure 6] show the specific capacity-cell voltage characteristics. At the start of charging or discharging (0 mAh / g), a large increase or decrease in the cell voltage is observed, respectively, especially at high charge / discharge current densities. This voltage drop is called the IR drop and is caused by the internal resistance of the cell. TEA·BF 4 In the case of EDLC using / PC (organic electrolyte), the IR drop increased as the amount of RHAC added increased. 4 When PC was used as the electrolyte, RHAC increased the internal resistance, decreasing the voltage shared in the formation of the electric double layer and lowering the specific capacitance. However, even when RHAC was added at 20 or 40%, the specific capacitance was only 0.01V at the highest charge / discharge current density (50mA / cm 2 ), the decrease in the specific capacitance retention was only 8%, and although RHAC reduced the rate characteristics, the extent of the decrease was small. On the other hand, EMIm·BF 4 In the EDLC using ionic liquid, the IR drop decreased as the amount of RHAC added increased. 2At the above high charge / discharge current densities, the addition of 20 or 40% RHAC achieved a higher specific capacitance than the addition of YP-50F alone. In particular, when RHAC was added at 20%, the specific capacitance was higher at low to medium charge / discharge current densities (0.01 to 10 mA / cm). 2 ), the specific capacitance was comparable to that of YP-50F alone, and the characteristics at high current densities were improved without degrading the characteristics at low and medium current densities. The EDLC using only RHAC did not show a higher specific capacitance than the EDLC using only YP-50F at all charge and discharge current densities, indicating that an improvement in rate characteristics appears only when an appropriate amount of RHAC is added to YP-50F. On the other hand, looking at the rate characteristics of each EDLC shown in [Figure 7], the electrolyte is TEA·BF 4 / PC and EMIm·BF 4 Regardless of which was used, by adding AP15, it was possible to achieve a specific capacitance close to that of an EDLC using YP-50F, but it was not possible to achieve a specific capacitance higher than that of YP-50F across the entire current density range. Looking at the specific capacitance-cell voltage characteristics in [Figures 8] and [Figures 9], the IR drop at high current density was not reduced by the addition of AP15, and AP15 had no effect on reducing the internal resistance of the EDLC.

[0032] (2) Measurement of the cycle characteristics of each EDLC cell and its specific capacity-cell voltage characteristics [Figure 10] and [Figure 11] show the cycle characteristics of each EDLC cell and its specific capacity-cell voltage characteristics. For the graph of cycle characteristics, the horizontal axis is the number of cycles, and the vertical axis is the specific capacitance. The graph shows the specific capacitance during discharge, not during charging. The specific capacitance maintenance rate during cycle testing is shown to the right of the cycle characteristics. In general, EDLCs are required to maintain their specific capacitance even when exposed to repeated charging and discharging. For the graph of specific capacitance-cell voltage characteristics, the horizontal axis is the specific capacitance, and the vertical axis is the cell voltage. The graph shows the number of cycles: 10, 10,000, 20,000, 50,000, and 100,000. As shown in Figure 10, the electrolyte is TEA·BF4 In cycle tests using / PC (organic electrolyte), the EDLC using only YP-50F showed the highest specific capacitance at the start of the cycle test. The EDLC with RHAC added had a lower specific capacitance at the start of the cycle test compared to the EDLC without additives, but showed a higher specific capacitance after 20,000 cycles. The EDLC using only RHAC had the lowest specific capacitance, but its retention rate was the highest. On the other hand, the electrolyte is EMIm BF 4 In cycle tests using RHAC (ionic liquid), the highest specific capacitance was measured for the EDLC using only YP-50F at the start of the cycle test. The EDLCs with 40% RHAC or no RHAC added did not show a higher specific capacitance than the EDLC using only YP-50F during the cycle test. However, by adding 20% ​​RHAC, a higher specific capacitance was obtained than the EDLC using only YP-50F after 10,000 cycles. The EDLC with 40% RHAC added did not have a large difference in specific capacitance compared to the EDLC using only YP-50F, but it had a higher retention rate. From the specific capacity-cell voltage characteristics in [Figure 11] and [Figure 12], it is clear that the electrolyte is TEA·BF 4 / EMIm・BF even with PC (organic electrolyte) 4 Even in the case of the ionic liquid, the addition of RHAC suppressed the increase in IR drop with increasing cycle number. 4 / PC (organic electrolyte) is 40%, EMIm BF 4 In the case of (ionic liquid), the increase in internal resistance due to charge / discharge cycles was significantly suppressed at 20% RHAC, and the increase in internal resistance due to charge / discharge cycles was suppressed. Looking at the cycle characteristics of each EDLC in [Figure 13], the electrolyte is TEA·BF 4 Even if PC (organic electrolyte) is used, EMIm BF 4 Even when an ionic liquid (AP15) was used, the addition of AP15 achieved a specific capacitance close to that of an EDLC using YP-50F, but a specific capacitance sufficiently higher than that of YP-50F could not be achieved at any cycle number. Looking at the specific capacitance-cell voltage characteristics in [Figure 8] and [Figure 9], the IR drop at high current density did not decrease with the addition of AP15, and AP15 had no effect on reducing the internal resistance of the EDLC. Regardless of which electrolyte was used, the specific capacitance of the EDLC with AP15 added was unchanged or worse than that of the EDLC without additive, and no higher specific capacitance than that of the EDLC cell containing only YP-50F was measured during the cycle test. From the specific capacitance-cell voltage characteristics in [Figure 14] and [Figure 15], regardless of the type of electrolyte, the effect of adding AP15 in reducing the IR drop was not clearly evident, and AP15 made almost no contribution to suppressing the increase in the internal resistance of the EDLC cell. The results of cycle tests conducted so far have demonstrated that simply adding a different type of activated carbon to the electrode activated carbon does not necessarily improve cycle characteristics, but that adding 10 to 50% activated carbon mainly composed of mesopores to activated carbon mainly composed of micropores can improve cycle characteristics regardless of the type of organic, ionic liquid, or electrolyte used.

[0033] 3. Electrochemical impedance test results The results of the electrochemical impedance test are shown in [Figure 16] to [Figure 19]. In the graphs of impedance characteristics, the vertical axis is the imaginary component of the impedance, and the horizontal axis is the real component of the impedance. A weak AC sine wave voltage with an amplitude of 5 mV is superimposed on the DC bias voltage in the EDLC cell. The real and imaginary components of the impedance are obtained while decreasing the frequency of the sine wave voltage from 100 kHz to 10 mHz. In general, as the frequency of the superimposed sine wave voltage decreases, the real component of the impedance increases uniformly. In other words, the minimum value of the real component of the impedance is measured at a frequency of 100 kHz, and the maximum value at a frequency of 10 mHz. Looking at [Figure 16], when the DC bias voltage was 0 V, the EDLCs in which the total solution resistance and charge transfer resistance was lower than that of the additive-free EDLC both before and after the cycle test were those that contained TEA·BF in the electrolyte. 4 / EDLC using PC (organic electrolyte) with 40% RHAC added, and EMIm BF4 The EDLC used ionic liquid and contained 20% or 40% RHAC. Looking at [Figure 17], when the DC bias voltage was 2.5 V, the EDLCs in which the total solution resistance and charge transfer resistance was lower than that of the additive-free EDLC both before and after the cycle test were those that contained TEA·BF in the electrolyte. 4 / EDLC using PC (organic electrolyte) with 40% or 100% RHAC added, and EMIm BF 4 The EDLC used ionic liquid and contained 20% or 40% RHAC. These results demonstrate that the addition of RHAC suppresses the increase in internal resistance, based on the IR drop in the specific capacity-cell voltage characteristics of the cycle test. The effect of RHAC in suppressing the increase in internal resistance was also confirmed by electrochemical impedance spectroscopy. On the other hand, the impedance characteristics of the EDLCs with AP15 added when a DC bias of 0 V and 2.5 V is applied are shown in [Figure 18] and [Figure 19]. The total solution resistance and charge transfer resistance of the EDLCs with AP15 added was not lower than that of the EDLCs without AP15 before the cycle test. 4 Only the EDLC using / PC and adding 20% ​​AP15 showed a slightly lower total solution resistance and charge transfer resistance at a bias of 2.5 V after the cycle test, but AP15 had only a slight effect in suppressing the increase in internal resistance. This result was not inconsistent with the change in IR drop in the specific capacitance-cell voltage characteristics measured in the cycle test.

[0034] 4. Analysis of the Electrodes by Scanning Electron Microscopy To investigate the microstructure of each of the EDLC electrodes, a scanning electron microscope (VE-8800, Keyence Corporation) was used to observe the surfaces of three types of electrodes: undegraded, degraded positive electrode, and degraded negative electrode. The undegraded electrodes were cut out with scissors to a size of 5 mm length x 5 mm width from coated and dried aluminum foil, and vacuum degassed at 140°C for 6 hours in the same manner as when assembling the EDLC cells. They were not immersed in the electrolyte. The degraded positive electrode and degraded negative electrode were prepared by disassembling each EDLC cell after the final impedance test, cutting the removed electrodes with scissors to a 45° arc shape, and vacuum degassing them at 80°C for 1.5 hours. As shown in [Figure 20], the electrolyte is TEA·BF 4 When / PC (organic electrolyte) was used, it was found that deposits had formed on the surface of the negative electrode after degradation of the EDLC made of 100% YP-50F, compared to the undegraded electrode. Compared to 100% YP-50F, the YP-50F 80% RHAC 20% and YP-50F 60% RHAC 40% and RHAC 100% did not show much difference on the electrode surface before and after degradation. As shown in [Figure 21], the electrolyte is EMIm BF 4 Similarly, when using ionic liquid, deposits were observed on the surface of the negative electrode of the 100% YP-50F EDLC after degradation compared to the undegraded electrode. Similarly, when comparing the 80% YP-50F / 20% RHAC, 60% YP-50F / 40% RHAC, and 100% RHAC samples with 100% YP-50F, there was little difference in the electrode surface before and after degradation. As shown in [Figure 22] and [Figure 23], when AP15 was added to the electrolyte, TEA·BF 4 / PC (organic electrolyte) and EMIm・BF 4 In all cases where (ionic liquid) was used, deposits were formed on the electrode surface after degradation compared to the undegraded electrode surface, and the gaps that existed before degradation were blocked. [Industrial Applicability]

[0035] According to the present invention, it is possible to manufacture an electric double layer capacitor (EDLC) that has a long cycle life, excellent rate characteristics, and is manufactured by a relatively simple method. Therefore, the present invention is useful not only in the electronic parts industry, but also in the automobile industry and power equipment industry, which have long product life spans and require EDLCs with a long cycle life.

Claims

1. An active material for an electric double layer capacitor, comprising activated carbon mainly having micropores and activated carbon mainly having mesopores, Activated carbon mainly composed of mesopores is rice husk activated carbon, which is an active material for electric double layer capacitors.

2. 2. The active material for electric double layer capacitors according to claim 1, wherein the weight ratio of the activated carbon mainly composed of micropores and the activated carbon mainly composed of mesopores is "(activated carbon mainly composed of mesopores) / (activated carbon mainly composed of micropores+activated carbon mainly composed of mesopores)=10 to 50 wt %", and the total weight ratio of the two types of activated carbon to the entire active material is 90 wt % or more.

3. 3. An electric double layer capacitor using, as one or both electrodes, an electrode in which the active material for an electric double layer capacitor according to claim 1 or 2 is used as an active material.

4. 4. The electric double layer capacitor according to claim 3, wherein the electrolytic solution used in the electric double layer capacitor is an organic electrolytic solution.

5. 5. The electric double layer capacitor according to claim 4, wherein the electrolyte used in the electric double layer capacitor is an ionic liquid.

Citation Information

Patent Citations

  • Electric double-layer capacitor

    JP2005243933A

  • Adjustment method of electrostatic capacity of electric double layer capacitor

    JP2007067034A

  • Electrodes for energy storage devices

    JP2010507264A

  • Electrochemical capacitor

    JP2014165435A

  • Polarizable electrode for electric double layer capacitor

    JP2016018808A